Integrated optics: Development and characterization of planar waveguides - Mosquera, Luis (1999)
In this paper, we show the first results obtained in the UNI, about the technology of elaboration and characterization of optical guides. This Work was initiated in August 98, in relation to a Workshop organized in our Lab by Prof. Mauro Lomer. We present here the basic theory, the applied elaboration Methods, the characterization process and results.